A rare case of necrotizing fasciitis of eyelid in a young immunocompetent lady- case report and review of literature - Venkataramani, Nithya; Muralidhar, Sonali; Sachidananda, Ravi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Necrotising fasciitis of the periorbital region is a rare condition where there is destruction of the periorbital soft tissue with potential of rapid spread causing significant morbidity and mortality. It is generally seen in immuno suppressed individuals following trivial trauma. Here we present a case of periorbital necrotising fasciitis in a young immonocompetent lady with emphasis on early identification and aggressive treatment to prevent loss of vision and mortality.